2016
DOI: 10.4137/cpath.s40497
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Gamma: Influence on Neural Stem Cell Function in Neurodegenerative and Neuroinflammatory Disease

Abstract: Interferon-gamma (IFNγ), a pleiotropic cytokine, is expressed in diverse neurodegenerative and neuroinflammatory conditions. Its protective mechanisms are well documented during viral infections in the brain, where IFNγ mediates non-cytolytic viral control in infected neurons. However, IFNγ also plays both protective and pathological roles in other central nervous system (CNS) diseases. Of the many neural cells that respond to IFNγ, neural stem/progenitor cells (NSPCs), the only pluripotent cells in the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 154 publications
(200 reference statements)
1
26
0
Order By: Relevance
“…In previous studies, TNF-α has contradictorily been shown to decrease, increase or have no effect on proliferation (Ben-Hur et al, 2003;Wong, Goldshmit and Turnley, 2004;Widera et al, 2006;Johansson, Price and Modo, 2008), while IFN-γ has either decreased or had no effect on proliferation (Ben-Hur et al, 2003;Wong, Goldshmit and Turnley, 2004;Widera et al, 2006;Johansson, Price and Modo, 2008). In consistent with our findings, a recent study showed that IFN-γ signaling via IFNGR1 and IFNGR2 receptors activates the JAK-STAT1 pathway, which eventually inhibits the proliferation of NPCs (Kulkarni, Ganesan and O'Donnell, 2016). TNF-α treatment has been shown to activate the nuclear factor kappa B pathway, which eventually leads to survival of the NPCs (Shih, Wang and Yang, 2015).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In previous studies, TNF-α has contradictorily been shown to decrease, increase or have no effect on proliferation (Ben-Hur et al, 2003;Wong, Goldshmit and Turnley, 2004;Widera et al, 2006;Johansson, Price and Modo, 2008), while IFN-γ has either decreased or had no effect on proliferation (Ben-Hur et al, 2003;Wong, Goldshmit and Turnley, 2004;Widera et al, 2006;Johansson, Price and Modo, 2008). In consistent with our findings, a recent study showed that IFN-γ signaling via IFNGR1 and IFNGR2 receptors activates the JAK-STAT1 pathway, which eventually inhibits the proliferation of NPCs (Kulkarni, Ganesan and O'Donnell, 2016). TNF-α treatment has been shown to activate the nuclear factor kappa B pathway, which eventually leads to survival of the NPCs (Shih, Wang and Yang, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…The data about the effects of IFN-γ, TNF-α and IL-6 on neuronal cells is contradictory or has not been studied in details (Ben-Hur et al, 2003;Wong, Goldshmit and Turnley, 2004;Sheng et al, 2005;Widera et al, 2006;Walter et al, 2011;Ye et al, 2013;Kulkarni, Ganesan and O'Donnell, 2016). First, expression of receptors for the cytokines IFN-γ, TNF-α and IL-6 in NPCs were studied; these receptors are necessary to transduce the signals to the cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the significant suppression of IFN-γ gene in CVB3-infected hNPCs proved to be an unexpected finding. IFN-γ, a pleiotropic cytokine, has a central role in regulating NSCs proliferation and quiescence [36,37]. Li et al previously demonstrated that K3 and K5 proteins of Kaposi's sarcoma-associated herpesvirus specifically target gamma interferon receptor 1 (IFN-γR1) and induce its ubiquitination, endocytosis, and degradation to downregulate IFN-γR1 surface expression, and, thereby, inhibit IFN-γ action [38].…”
Section: Discussionmentioning
confidence: 99%
“…In comparing the overlap of DEGs with ASD-associated genes, the GO process category that was most significant was "interferon-gamma (IFNγ) signaling." IFNγ has a complex role in mediating immune activation in the central nervous system and is believed to play an important role in the biology of ASD [57,58]. While peripheral cytokine patterns have been noted to be different in BPI, there have been conflicting reports on the role of IFNγ in BPI [59,60].…”
Section: Analysis Of Protein-protein Interaction (Ppi) Networkmentioning
confidence: 99%